PENERAPAN PENDEKATAN QUANTUM TEACHING DALAM PEMBELAJARAN IPA DI KELAS V SDN 2 JOGOMERTAN - RIFAI, AFIF (KALAM CENDEKIA PGSD KEBUMEN, 2012)
Abstract: Applying Of Approach of Quantum Teaching in Study of Sains in Class of V SDN 2 Jogomertan. Target of this research is mendeskripsikan applying of approach of Quantum Teaching in study of Sains in class of V Elementary School and improve result learn Sains pass/through approach of Quantum Teaching in class of V Elementary School. This Research use technique Research Of Action Class. Procedure research of class action in the form of planning, execution, perception, and refleksi. Execution of action executed in three cycle, each cycle three meeting. Its result indicate that applying of approach of Quantum Teaching can improve result and study learn Sains in class of V Elementary School. Keyword: Approach Of Quantum Teaching, Study of Sains   Abstrak: Penerapan Pendekatan Quantum Teaching dalam Pembelajaran IPA di Kelas V SDN 2 Jogomertan. Tujuan penelitian ini adalah mendeskripsikan penerapan pendekatan Quantum Teaching dalam pembelajaran IPA di kelas V Sekolah Dasar dan meningkatkan hasil belajar IPA melalui pendekatan Quantum Teaching di kelas V Sekolah Dasar. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas. Prosedur penelitian tindakan kelas berupa perencanaan, pelaksanaan, pengamatan, dan refleksi. Pelaksanaan tindakan dilaksanakan dalam tiga siklus, masing-masing siklus tiga pertemuan. Hasilnya menunjukkan bahwa penerapan pendekatan Quantum Teaching dapat meningkatkan  pembelajaran dan hasil belajar IPA di kelas V Sekolah Dasar.   Kata Kunci: Pendekatan Quantum Teaching, Pembelajaran IPA